GLOBALIZATION PROCESS AND MISSIONARY MOVEMENT (Scientific journal of the Fergana State University, 2023)
The article is devoted to the analysis of the problem of ensuring the safety of society and the stability of the country, aggravating in recent years with the spread of missionary work and proselytism. It reveals in detail the goals and nature of this extremist movements, which contribute to the emergence of ideological threats to the peaceful and secure life of the peoples of the world. It has been given the recommendations on struggling against dangerous phenomenon on legal base.